The power of positive emotions in challenging times: A positive psychology intervention program - Navarez, Joel C. (Animo Repository, 2023)
Schools have taken the initiative to establish programs pertaining to mental health and well-being in response to the rising number of students who may face distress and mental health issues following the Covid-19 outbreak (World Health Organization, 2021). The goal of this study was to design a positive psychology group intervention program targeted at enhancing college students’ subjective well-being by boosting their ability to feel good even in the face of trying circumstances. The hedonic aspect of well-being and the first component of the PERMA Theory, which is concerned with happiness as a whole, is positive emotion (Seligman, 2011). Positive mental health is anticipated to develop and flourish when pleasant feelings are nurtured. A needs and asset assessment were conducted when the proposed intervention program was being developed in order to justify its utility to the intended participants, who are first-year college students already enrolled at the institution. The framework for the experiential learning cycle was used to create the curriculum. A five-session program that can be delivered both in-person and online was developed as a result of this program development research. This program included activities that would assist participants to become aware of and build on their resources and assets that would help them deal with issues they would experience in the future, with a focus on positive feelings. This program may be piloted to assess its effectiveness.